Comales of Tzompantepec and paleosols: a case study - Yolanda Ramos-Galicia; Claudia Hidalgo-Moreno; Sergey Sedov; Thomas Poetsch (Revista Mexicana de Ciencias Geológicas)
Use of paleosols as the source of material for industries and handcrafts in past and present is one important aspect of applied paleopedological research. We studied in Tlaxcala State, Mexico, a stratum mined for traditional ceramic production to determine whether it is a paleosol and which properties made it appropriate for this handcraft. Morphological, micromorphological and pedochemical data showed that this stratum has properties of a buried, well developed Luvic Andosol. It has much higher clay content than overlying soils and sediments, due to pedogenetic processes: weathering of primary volcanic minerals (especially volcanic glass) and clay illuviation. We suppose that the suitable ratio between amorphous components and crystalline clay provides the combination of properties desirable for elaboration of ceramic.